Jasmonic acid and salicylic acid play minor roles in stomatal regulation by CO2, abscisic acid, darkness, vapor pressure deficit and ozone. (14th August 2021) - Zamora, Olena; Schulze, Sebastian; Azoulay‐Shemer, Tamar; Parik, Helen; Unt, Jaanika; Brosché, Mikael; Schroeder, Julian I.; Yarmolinsky, Dmitry; Kollist, Hannes
SUMMARY: Jasmonic acid (JA) and salicylic acid (SA) regulate stomatal closure, preventing pathogen invasion into plants. However, to what extent abscisic acid (ABA), SA and JA interact, and what the roles of SA and JA are in stomatal responses to environmental cues, remains unclear. Here, by using intact plant gas‐exchange measurements in JA and SA single and double mutants, we show that stomatal responsiveness to CO2, light intensity, ABA, high vapor pressure deficit and ozone either did not or, for some stimuli only, very slightly depended upon JA and SA biosynthesis and signaling mutants, including dde2, sid2, coi1, jai1, myc2 and npr1 alleles. Although the stomata in the mutants studied clearly responded to ABA, CO2, light and ozone, ABA‐triggered stomatal closure in npr1‐1 was slightly accelerated compared with the wild type. Stomatal reopening after ozone pulses was quicker in the coi1‐16 mutant than in the wild type. In intact Arabidopsis plants, spraying with methyl‐JA led to only a modest reduction in stomatal conductance 80 min after treatment, whereas ABA and CO2 induced pronounced stomatal closure within minutes. We could not document a reduction of stomatal conductance after spraying with SA. Coronatine‐induced stomatal opening was initiated slowly after 1.5–2.0 h, and reached a maximum by 3 h after spraying intact plants. Our results suggest that ABA, CO2 and light are major regulators of rapid guard cell signaling, whereas JA and SA could play only minor roles in the whole‐plant stomatal response to environmental cues in Arabidopsis and Solanum lycopersicum (tomato). Significance Statement: Jasmonic acid (JA) and salicylic acid (SA) can promote stomatal closure; however, the roles of these hormones in stomatal responses to environmental cues remain unclear. Here, we show that stomatal responsiveness to CO2, light intensity, abscisic acid, high vapor pressure deficit and ozone either did not or, for some stimuli only, very slightly depended on JA and SA.